Effects of fiscal deficit and money M2 supply on inflation: Evidence from selected economies of Asia - Van Bon Nguyen (Journal of Economics, Finance and Administrative Science, 2015)
A sustained high growth rate of gross domestic product at a low inflation is one of the main goals of the majority of macroeconomic policies, so keeping the price stability plays an important role in determining the growth rate of output. This paper empirically investigates effects of fiscal deficit and broad money M2 supply on inflation in Asian countries, namely Bangladesh, Cambodia, Indonesia, Malaysia, Pakistan, Philippines, Sri Lanka, Thailand, and Vietnam in the period of 1985-2012. By applying the Pooled Mean Group (PMG) estimation-based error correction model and the panel differenced GMM (General Method of Moment) Arellano-Bond estimator, the study finds out broad money M2 supply has significantly positive impact on inflation only in the method of PMG estimation whereas fiscal deficit, government expenditure and interest rate are the statistically significant determinants of inflation in both methods of estimation – – El sostenimiento de una elevada tasa de crecimiento del producto bruto interno a baja inflación es uno de los principales objetivos de la mayoría de las políticas macroeconómicas, por lo que el mantenimiento de la estabilidad de los precios juega un papel relevante en la determinación del índice de crecimiento del output. Este documento investiga empíricamente los efectos del déficit fiscal y el suministro amplio de dinero M2 sobre la inflación en los países asiáticos, en concreto Bangladesh, Camboya, Indonesia, Malasia, Paquistán, Filipinas, Sri Lanka, Tailandia, y Vietnam durante el periodo comprendido entre 1985 y 2012. Aplicando el modelo de corrección basado en la estimación de Pooled Mean Group (PMG) y el estimador Arellano-Bond del Método Generalizado de Momentos (MGM) del panel diferenciado, el estudio llega a la conclusión de que el amplio suministro de dinero M2 tiene un impacto considerablemente positivo sobre la inflación utilizando únicamente el método de la estimación de PMG, mientras que el déficit fiscal, el gasto gubernamental y los tipos de interés constituyen determinantes estadísticamente significativos de la inflación en ambos métodos de cálculo.
Keywords: O15; 330; Fiscal deficit; Broad money M2 supply; Inflation; PMG estimation; Differenced panel GMM estimator; Asian countries; Déficit fiscal; Suministro amplio de dinero M2; Inflación; Estimación PMG; Estimador MGM del panel diferenciado; Países asiáticos